2014
DOI: 10.1007/s10921-014-0260-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between AC Core Loss and Surface Magnetic Barkhausen Noise in Electric Motor Steel

Abstract: Core loss is a significant source of energy loss in electric motor steel laminates. Therefore, there is interest in monitoring the quality and consistency of laminates at various stages of manufacturing. The purpose of this study was to investigate the feasibility of using surface magnetic Barkhausen noise for the evaluation of AC core loss, and further, to examine potential origins of magnetic loss in nonoriented electrical steel. Core loss values were measured by a single sheet tester and Barkhausen noise me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In addition, work by Samimi et al has shown that for NOES, the MBN energy correlated inversely with loss. [15] A similar result was shown by Birsan et al for GOES. [21] Consequently, it is believed that MBN energy can also be applied to NOES to study the effects of misorientation and orientation, and be correlated to loss properties.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…In addition, work by Samimi et al has shown that for NOES, the MBN energy correlated inversely with loss. [15] A similar result was shown by Birsan et al for GOES. [21] Consequently, it is believed that MBN energy can also be applied to NOES to study the effects of misorientation and orientation, and be correlated to loss properties.…”
Section: Introductionsupporting
confidence: 80%
“…[15] Similarly, the TF variations for the test locations also showed variations on the order of variations observed between samples of different manufacturers. [6] This demonstrated that local variations in microstructural parameters and magnetic properties were present in the NOES strips.…”
Section: Magnetic Properties Vs Texture Parameters and Orientationmentioning
confidence: 85%
See 3 more Smart Citations